Optimasi Strategi Komunikasi dan Negosiasi BAZNAS Dharmasraya dalam Menggalang Zakat Profesi Guru di Dinas Pendidikan Kabupaten Dharmasraya - Sri Lestari Nengsih; Ernita Arif; Sarmiati Sarmiati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research aims to identify the lobbying and negotiation strategies employed by BAZNAS Dharmasraya Regency in collecting professional zakat from teachers within the Dharmasraya Regency's Education Office. The research adopts a qualitative approach with a constructivist paradigm and employs a case study methodology. Informants were selected using purposive sampling, and data were collected through in-depth interviews, observations, and documentation. Data analysis followed the Miles and Huberman approach, involving data reduction, data presentation, and conclusion drawing, with validation achieved through source triangulation. The findings of this research reveal that BAZNAS Dharmasraya Regency follows the lobbying and negotiation stages as outlined by Cutlip and Center, encompassing Fact Finding, Planning, Communication, and Evaluation stages. This process involves persuasive communication techniques, both interpersonal and group, facilitating the smooth conveyance of messages without coercion. As a result of these lobbying and negotiation strategies, BAZNAS successfully collected professional zakat from elementary and junior high school teachers in Dharmasraya Regency for the period of October-December 2022. This accomplishment led to an increase in the total zakat received by BAZNAS Dharmasraya Regency for the year 2022.